STANDARDIZATION OF CHITRAKADI VATI: AN AYURVEDIC POLYHERBAL FORMULATION (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Standardization of herbal formulation is essential in order to assess the quality, purity, safety and efficacy of drugs. World health organization (WHO) in 1999 has given a detail protocol for the standardization of herbal drugs comprising of a single content but very little literature is available for the standardization of polyherbal formulations. Chitrakadi Vati is official in ayurvedic formulary of India and it is prescribed for the treatment of irritable bowel syndrome, rheumatoid arthritis and loss of appetite. In the present work, attempt has been made to develop a chromatographic method for standardization of Chitrakadi Vati. All raw materials used were standardized by macroscopic, microscopic and physico-chemical parameters. Piperine in Piper nigrum and Piper longum; Plumbagin in Plumbago zeylanica are active components in the formulation and can be considered as marker compounds. A simple, rapid, precise, accurate and reproducible High Performance Thin Layer Chromatography (HPTLC) densitometric method was developed. The separation was performed on TLC aluminium plates precoated with silica gel 60 F254, good separation was achieved in the mobile phase of toluene: ethyl acetate: formic acid (7.5:2.5:0.5 v/v/v) and densitometry determination of piperine (0.39 ± 0.02) and plumbagin (0.70 ± 0.02) was carried out at single wavelength scanning at 280 nm. The developed method has been validated as per ICH (International conference on harmonization) guidelines. The developed and validated HPTLC method was applied for standardization of Chitrakadi Vati by detection and quantification of markers piperine and plumbagin simultaneously from in-house and marketed formulations.